INSONLAR MULOQOT VOSITASITALARI VA ZAMONAVIY TILSHUNOSLIKDA ASSOSATIV XOTIRANING AHAMIYATI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article sheds light on the level of importance of language as a means of communication and other important factors for communication in the era when people in different parts of the world can easily communicate. Also, the associative memory, which is important for receiving and storing information in the human mind, its functional properties and its importance for us will be revealed.
Keywords: modern linguistics, classical linguistics, memory, associative memory, understanding.